Nutrition and diet theraphy - Townsend, Carolynn E. (New York : Delmar Publishers Inc., 1985)
This was written for practical and vocational nursing students, beginning students in other health care professions, and students enrolled in food service and dietetic technician/assistant programs.
Sect. 1. Fundamentals of Nutrition -- Ch. 1. The Relationship of Food and Health -- Ch. 2. Planning a Healthy Diet -- Ch. 3. Digestion, Absorption, and Metabolism -- Ch. 4. Carbohydrates -- Ch. 5. Lipids, or Fats -- Ch. 6. Proteins -- Ch. 7. Vitamins -- Ch. 8. Minerals -- Ch. 9. Water -- Sect. 2. Maintenance of Health Through Good Nutrition -- Ch. 10. Food-Related Illnesses and Allergies -- Ch. 11. Diet During Pregnancy and Lactation -- Ch. 12. Diet During Infancy -- Ch. 13. Diet During Childhood and Adolescence -- Ch. 14. Diet During Young and Middle Adulthood -- Ch. 15. Diet During Late Adulthood -- Sect. 3. Diet Therapy -- Ch. 16. Diet and Weight Control -- Ch. 17. Diet and Diabetes Mellitus -- Ch. 18. Diet and Cardiovascular Disease -- Ch. 19. Diet and Renal Disease -- Ch. 20. Diet and Gastrointestinal Problems -- Ch. 21. Diet and Cancer -- Ch. 22. Diet and Surgery, Enteral and Parenteral Nutrition, Burns, Infections, and AIDS -- Ch. 23. Nutritional Care of Patients.
Keywords: NUTRITION